Respuesta :
Answer:
A) x = 1/2
B) m = -4
n = -3
Step-by-step explanation:
A)
[tex]15-0.5(4x-2)+4x=17[/tex]
Expand the brackets:
[tex]\implies 15-2x+1+4x=17[/tex]
Collect and combine like terms:
[tex]\implies 2x+16=17[/tex]
Subtract 16 from both sides:
[tex]\implies 2x=1[/tex]
Divide both sides by 2:
[tex]\implies x = \dfrac12[/tex]
B) Equation 1: n = m + 1
Equation 2: m = 2n + 2
Rewrite equation 1 to make m the subject:
m = n - 1
Subtract m = n - 1 from equation 2 to eliminate m:
0 = n + 3
Solve for n:
n = -3
Substitute n = -3 into either of the original equations and solve for m:
m = 2(-3) + 2
⇒ m = -4